Negative electrode material, preparation method thereof and potassium ion battery

By introducing arsenic-doped graphene, anchoring layered stannous sulfide into the negative electrode material of potassium ion battery, and introducing phosphate ions in situ, forming a PO4-SnS@AsG structure, the cyclic stability of the existing potassium ion battery negative electrode material is solved. The problem of insufficient performance and capacity achieves high dynamic performance and long-term cycle stability.

CN119400841AActive Publication Date: 2025-02-07HUNAN JAPRUI TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411977207.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-07
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In existing potassium ion batteries, when commercial graphite is used as the negative electrode material, its cycle stability is low, capacity is low, and the volume changes during charging and discharging, resulting in poor electrochemical performance and difficult to meet high specific capacity and long stable energy storage devices. Requirements.

Method used

Arsenic-doped graphene is used as the basis for the negative electrode material, and phosphate ions are introduced in situ by anchoring layered stannous sulfide (SnS) and introducing phosphate ions in situ to form a PO4-SnS@AsG structure. This structure is prepared by hydrothermal reaction and annealing treatment, which improves the conductive properties and cyclic stability of the material.

Benefits of technology

It significantly improves the dynamic performance and cycle stability of the negative electrode material, can maintain good electrochemical performance during high specific capacity and long-term energy storage, and meets the needs of high-performance energy storage equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400841A_ABST
    Figure CN119400841A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material. The negative electrode material comprises arsenic-doped graphene, layered stannous sulfide anchored on the arsenic-doped graphene, and phosphate ions introduced between stannous sulfide layers in situ. The negative electrode material provided by the invention has high conductivity, high cycle stability and high dynamic performance. The invention further provides a preparation method of the negative electrode material. The preparation method is simple to operate. The invention also provides an application of the negative electrode material in a potassium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of potassium-based energy storage devices, and in particular to a negative electrode material and a preparation method thereof, and a potassium ion battery. Background Art

[0002] At present, the development of lithium-based energy storage devices is limited by resource scarcity and high cost. New energy storage devices are urgently needed to solve current environmental and resource problems. Potassium-ion batteries (PIBs) have attracted widespread attention in recent years as an ideal alternative to potassium-ion batteries due to their high earth abundance and low potassium cost. + Not only does it have the advantage of higher energy density due to its lower redox potential, but K + It can also undergo intercalation reaction with commercial graphite negative electrode, which lays a research foundation for the practical application of PIBs in the future. However, when commercial graphite is used as the negative electrode material, its electrochemical performance is often poor due to low cycle stability, low capacity, large volume change during charge and discharge leading to collapse of graphite skeleton, etc., and it is difficult to meet the requirements of high specific capacity and long-term stable energy storage devices. Therefore, the development of efficient and stable potassium storage negative electrode materials is a top priority for realizing high-performance energy storage devices. Summary of the invention

[0003] The purpose of the present application is to provide a negative electrode material and a preparation method thereof and a potassium ion battery. The negative electrode material has high kinetic performance and excellent cycle stability.

[0004] In a first aspect, the present application provides a negative electrode material, which includes: arsenic-doped graphene, layered stannous sulfide anchored on the arsenic-doped graphene, and phosphate ions in-situ introduced between the stannous sulfide layers.

[0005] In some embodiments, the mass content of the arsenic-doped graphene is 4%-8% relative to the total weight of the negative electrode material.

[0006] The second aspect of the present application also provides a method for preparing the negative electrode material described in the first aspect of the present application, comprising the following steps: Tin source, arsenic pentoxide, sodium hydroxide, phosphorus source, and thiourea are sequentially added to a graphene oxide dispersion having a concentration of 0.4-1.0 mg / mL, and the mixture is stirred and dissolved to form a precursor solution. The precursor solution is subjected to a hydrothermal reaction to obtain a precursor powder, The precursor powder is annealed to obtain the negative electrode material.

[0007] In some embodiments, the hydrothermal reaction comprises: o C-180 o C for 10-12 h.

[0008] In some embodiments, the annealing treatment includes 2-5 o C / min annealing to 500 o C-600 o C, keep warm for 4-6 h.

[0009] In some embodiments, the tin source is SnCl 4 ·5H 2 O.

[0010] In some embodiments, the phosphorus source is selected from phytic acid or phosphoric acid.

[0011] In some embodiments, in the precursor solution, the mass ratio of graphene oxide, arsenic pentoxide, sodium hydroxide, tin source, phosphorus source, and thiourea is 1-3:26:24:144:55:6.

[0012] In some embodiments, the precursor solution is subjected to high-energy ball milling before the hydrothermal reaction.

[0013] The third aspect of the present application also provides a potassium ion battery, comprising the negative electrode material described in the first aspect of the present application.

[0014] In some embodiments, the potassium ion battery includes a potassium ion secondary battery and a potassium ion full battery.

[0015] In the negative electrode material provided by the present application, the electronic structure of graphene can be effectively changed by arsenic doping graphene, showing more active sites and significantly improving the conductivity of the material. And the changes in these electronic properties can reduce the reaction energy gap, which is beneficial to the electron transfer during the redox reaction. By anchoring the layered stannous sulfide on the arsenic-doped graphene, it is beneficial to improve the conductivity of the negative electrode material, realize the rapid transmission of potassium ions, and improve the kinetic performance of the electrode material during the full charge and discharge process. The phosphate ions introduced in situ between the stannous sulfide (SnS) layers can expand the lattice spacing in the SnS crystal, which is beneficial to alleviate the lattice expansion during the potassium insertion process, so that the electrode material maintains a longer cycle stability during repeated charge and discharge. The phosphate ions introduced in situ between the stannous sulfide (SnS) layers can adjust the electronic structure of the SnS crystal, and the Sn-OP bridging covalent bond is used as an electronic bridge, which effectively shortens the ion diffusion distance and promotes the storage kinetics of potassium ions. The preparation method of the negative electrode material of the present application uses arsenic oxide and sodium hydroxide as raw materials, and dopes arsenic atoms into the carbon structure of graphene through hydrothermal reaction and annealing treatment, and introduces phosphate ions into the interlayer of tin sulfide (SnS), thereby expanding the interlayer distance between graphene and tin sulfide, and improving the potassium ion storage kinetics of the prepared negative electrode material. The method of the present application is simple and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the implementation modes of the present application, the drawings required for use in the description of the implementation modes will be briefly introduced below. Obviously, the drawings described below are only some implementation modes of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 This is a scanning electron microscope (SEM) image of the negative electrode material prepared in Example 1 of the present application.

[0018] Figure 2 This is a transmission electron microscope (TEM) image of the negative electrode material prepared in Example 1 of the present application.

[0019] Figure 3 This is the infrared spectrum of the negative electrode material prepared in Example 1 of the present application.

[0020] Figure 4 It is a comparison chart of the battery rate cycle performance of Examples 1 and 3 of the present application and Comparative Examples 1-2.

[0021] Figure 5 It is a comparison chart of the high current cycle performance of Examples 1 and 4 of the present application and Comparative Example 1.

[0022] Figure 6 The battery K of Example 1 and Comparative Example 1 of the present application + Diffusion rate comparison chart.

[0023] Figure 7 This is an energy density cycling performance diagram of the full battery of Example 6 of the present application at a rate current density. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0026] Transition metal sulfides (TMSs) have shown considerable theoretical capacity in potassium storage due to their multi-electron reactions and multi-reaction mechanisms. Tin sulfide (SnS) is a two-dimensional (2D) transition metal sulfide with high theoretical capacity and a unique layered structure. However, SnS has inherently poor electrical conductivity, resulting in large ion diffusion barriers, unsatisfactory intrinsic conductivity, and its layered structure has a high conductivity at higher K. + Severe structural collapse and agglomeration are very likely to occur during the potassium insertion / depotassium process, triggering irreversible phase changes, causing the active materials to pulverize and fall off the current collector and continuous side reactions, ultimately resulting in poor rate capability and cycle stability.

[0027] In view of this, the present application provides a negative electrode material, which includes arsenic-doped graphene, layered stannous sulfide anchored on the arsenic-doped graphene, and phosphate ions in-situ introduced between the stannous sulfide layers.

[0028] In the present application, arsenic-doped graphene changes the electronic structure of graphene, showing more active sites and significantly improving its conductivity. And these changes in electronic properties can reduce the energy gap, which is beneficial to electron transfer during redox reactions. In addition, it exposes more active sites and improves the reactivity of the material. By anchoring layered stannous sulfide to arsenic-doped graphene through, for example, van der Waals forces, it is beneficial to improve the structural stability and electronic conductivity of the negative electrode material, achieve rapid transmission of potassium ions, and improve the kinetic performance of the electrode material during full charge and discharge. The in-situ introduction of phosphate ions between stannous sulfide (SnS) layers can expand the lattice spacing in the SnS crystal, thereby relieving the lattice expansion during potassium insertion, so that the electrode material maintains a longer cycle stability during repeated charge and discharge. The in-situ introduction of phosphate ions between stannous sulfide (SnS) layers can adjust the electronic structure of the SnS crystal, and the Sn-OP bridging covalent bond is used as an electronic bridge, which effectively shortens the ion diffusion distance and promotes the storage kinetics of potassium ions.

[0029] In some embodiments, the mass content of the arsenic-doped graphene is 4%-8% relative to the total weight of the negative electrode material. This helps prevent the SnS particles anchored to the graphene surface layer from aggregating during the cycle; it also improves the conductivity of the composite electrode material and can buffer the volume change of the electrode during potassium storage. Secondly, the insertion of phosphate ions into the two-dimensional SnS interlayer can not only adjust the microscopic morphology of SnS, but also form Sn-OP bridging covalent bonds between the SnS interlayers, adjusting the interlayer spacing and electronic structure of SnS.

[0030] The present application also provides a method for preparing the above-mentioned negative electrode material, comprising the following steps: Add tin source, arsenic pentoxide, sodium hydroxide, phosphorus source and thiourea to a graphene oxide dispersion having a concentration of 0.4 mg / mL-1.0 mg / mL, stir and dissolve, and form a precursor solution. The precursor solution is subjected to a hydrothermal reaction to obtain a precursor powder, The precursor powder is annealed to obtain the negative electrode material.

[0031] In the preparation method of the present application, arsenic pentoxide is an acidic oxide, which reacts with sodium hydroxide to form sodium arsenate during the hydrothermal reaction, and then the arsenate is incorporated into the carbon lattice of graphene during the annealing process. In addition, the SnS nanosheets with a two-dimensional structure are anchored on the arsenic-doped graphene sheets by a combined hydrothermal-annealing method, and phosphate ions are introduced in situ into the SnS interlayer to prepare the negative electrode material (PO4-SnS@AsG) of the present application. The negative electrode material has an extended interlayer spacing, which is beneficial to improving the cycle stability and kinetic performance of the negative electrode material. The method of the present invention uses a combined hydrothermal-annealing method to simultaneously complete the doping of arsenic into graphene, the synthesis of SnS and the insertion of phosphate ions during the preparation process, and the operation is simple.

[0032] In the present application, graphene oxide can be prepared by methods known to those skilled in the art or can be obtained commercially. Exemplarily, graphene oxide can be prepared by methods such as Hummers, Brodie, and Staudenmaier. In some embodiments, the preparation method of the graphene oxide dispersion of the present application includes: using natural graphite powder as a raw material, modifying it by the Hummers method to prepare a flaky GO solution; taking the GO solution and ultrasonicating it at room temperature for 5-6 h.

[0033] Among them, the Hummers method refers to mixing graphite powder with concentrated sulfuric acid, adding potassium permanganate to react to generate manganese heptoxide, continuing the reaction in an ice water bath to generate graphite oxide, adding hydrogen peroxide to terminate the reaction, and peeling the graphite flakes into graphene oxide through vigorous stirring. After multiple centrifugal washings with deionized water, the graphene oxide forms a stable, light brown single-layer suspension in water.

[0034] In the present application, a tin source, arsenic pentoxide, sodium hydroxide, a phosphorus source, and thiourea are sequentially added to a graphene oxide dispersion and stirred and dissolved to form a precursor solution, and then a precursor is prepared by a hydrothermal method. In some embodiments, before the hydrothermal reaction, the precursor is easily subjected to high-energy spheroidal graphite treatment. Through high-energy spheroidal graphite treatment, on the one hand, the graphite material is mechanically ground to destroy its layered structure so that it gradually peels off a single layer of graphene; on the other hand, the raw materials in the precursor solution are mixed more evenly, which is conducive to the uniform doping of arsenic atoms into the graphene crystal structure and the uniform insertion of phosphate ions into the tin sulfide interlayer. In the present application, high-energy spheroidal graphite treatment can be carried out using conventional equipment in the art. For example, high-energy spheroidal graphite can be carried out using a vibrating high-energy ball mill. In some embodiments, the spheroidal graphite rate of high-energy spheroidal graphite is 2700-4000 rpm; the ball milling time is 2-3h.

[0035] The method of the present application obtains a precursor by a hydrothermal reaction, and the operation steps and reaction conditions are simple. Exemplarily, the step of preparing a precursor solution includes: ultrasonicating graphene oxide into a few-layer graphene oxide, adding an appropriate amount of tin source, arsenic pentoxide and sodium hydroxide to the few-layer graphene oxide dispersion, dissolving under stirring, keeping stirring, then adding an appropriate amount of phosphorus source, adding an appropriate amount of thiourea after mixing evenly, and mixing evenly to obtain a precursor solution. It is understood that stirring can be carried out by means known in the art, such as by magnetic stirring, mechanical stirring and other methods. The present application does not specifically limit the stirring time, and all the raw materials are stirred until dissolved and mixed evenly. Those skilled in the art can select the stirring time as needed. Exemplarily, each stirring time is 0.5h.

[0036] In some embodiments, in the precursor solution, the mass ratio of graphene oxide, tin source, arsenic pentoxide, sodium hydroxide, phosphorus source, and thiourea is 1-3:26:24:144:55:6.

[0037] In some embodiments, the tin source is SnCl 4 ·5H 2 O.

[0038] In some embodiments, the phosphorus source is selected from phytic acid or phosphoric acid.

[0039] In some embodiments, the hydrothermal reaction comprises: o C-180 oC is maintained for 10h-12h. It is understood that the hydrothermal reaction can be carried out by equipment or means known to those skilled in the art. Exemplarily, the hydrothermal reaction is carried out in a polytetrafluoroethylene-lined stainless steel autoclave. After the hydrothermal reaction is completed, the obtained black precipitate is separated and washed several times, and the precursor powder is obtained after drying. Separation can be carried out by filtering, centrifugation and the like. In some embodiments, washing includes washing with anhydrous ethanol and deionized water for 3 times respectively. The reactants and impurity ions that have not reacted completely on the surface of the precursor are removed by washing. In some embodiments, drying is performed by freeze drying. Freeze drying is used to allow the water to sublime directly, and the prepared material is more fluffy, which is beneficial to increase the specific surface area of ​​the negative electrode material, thereby improving the kinetic properties of the material.

[0040] In the present application, the precursor powder is annealed to obtain the negative electrode material. The annealing treatment allows arsenic atoms to be further doped into the carbon matrix and further improves the crystallinity of SnS, thereby helping to improve the structural stability of the prepared negative electrode material.

[0041] In some embodiments, the annealing treatment includes 2-5 o C / min annealing to 500 o C-600 o C, and keep warm for 4h-6h. The negative electrode material obtained by annealing in the above steps has better cycle stability and kinetic performance. For example, the annealing temperature can be 500 o C. 550 o C. 600 o C or a value between any two of the values. As the annealing temperature increases, the annealing process may cause the destruction of the lamella structure of stannous sulfide and the loss of a portion of phosphate ions. In some preferred embodiments, the annealing temperature is 500 o C-550 o C. By making the annealing temperature within this range, the damage to the stannous sulfide structure and the loss of phosphate ions caused by the annealing treatment can be reduced, and the cycle stability and capacity retention rate of the material can be further improved.

[0042] The present application also provides a potassium ion battery, comprising the above-mentioned negative electrode material. The negative electrode material of the present application is used to prepare the negative electrode plate of the potassium ion battery, which can provide the potassium ion battery with improved cycle stability and kinetic performance.

[0043] In some embodiments, the potassium ion battery includes a potassium ion secondary battery and a potassium ion full battery.

[0044] The present application will be further described below with reference to specific embodiments. Example

[0045] It is understood that the following examples are exemplary and are only used to explain the present application and cannot be construed as limiting the present application. The specific techniques and conditions not marked in the examples are carried out according to the techniques or conditions described in the literature of the art or according to the product instructions. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0046] Sources of reagents used in the following examples: stannous chloride pentahydrate, arsenic pentoxide, sodium hydroxide, thiourea, phytic acid, and potassium metal were all purchased from Aladdin Chemical Reagent Co., Ltd.

[0047] The manufacturers and models of the instruments used in the experiment are as follows: The desktop centrifuge is a TG16-WS desktop centrifuge produced by Hunan Xiangyi Instrument Co., Ltd.; The single temperature zone tube furnace is the OTF-1200X single temperature zone tube furnace of Hefei Kejing Material Technology Co., Ltd.; The magnetic stirrer was the HJ-6B magnetic stirrer produced by Shanghai Yidian Scientific Instrument Co., Ltd. The polytetrafluoroethylene high-pressure reactor was from Shanghai Baikal Technology Co., Ltd.; The electrochemical workstation is the Lvium electrochemical workstation from IVIUM Technologies BV of the Netherlands; The battery testing system is the LAND-CT2001A battery testing system of Wuhan Landian Electronics Co., Ltd.; The precision balance is an EX125DZH balance from Ohaus Instruments; The vibrating high-energy ball mill is Kejing MSK-SFM-12M; The glove box was an MB-Labstar glove box from Braun Inert Gas Co., Ltd.

[0048] Example 1 Preparation of negative electrode materials Natural graphite powder was used as raw material and the GO solution was prepared by Hummers method. The concentration was 0.4 mg / mL -1 , 65 mL of GO dispersion was ultrasonicated at room temperature for 5 h to form a few-layer graphene oxide dispersion.

[0049] 0.701 g SnCl 4 ·5H 2 O was dissolved in the above graphene oxide dispersion under magnetic stirring and stirred for 0.5 h until no obvious particles were present.

[0050] Add 0.216 g of arsenic pentoxide and 1.294 g of sodium hydroxide to the above solution and continue stirring for 0.5 h until the solution is homogeneous.

[0051] Add 1.0 mL of phytic acid to the above solution and continue stirring for 0.5 h until the solution is homogeneous.

[0052] 0.152 g of thiourea was added to the above solution and stirred for 1 h until the solution was uniform to obtain a precursor solution.

[0053] The precursor solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at a temperature of 180 o C, maintain for 12 h.

[0054] The black precipitate obtained by the hydrothermal reaction was centrifuged, washed three times with anhydrous ethanol and deionized water respectively, and then freeze-dried at -80°C for 12 h to obtain a black precursor powder.

[0055] The black precursor powder was placed in a magnetic boat and placed in a tube furnace filled with argon at 2 o C / min annealing to 500 o C, and kept warm for 4 h, the negative electrode material (denoted as PO 4 -SnS@AsG).

[0056] The obtained negative electrode material was tested by electron scanning electron microscopy (SEM) and transmission electron microscopy (TEM). During the TEM observation, three points on the material were randomly selected and the average arsenic content at the three selected points was tested using TEM accessory energy dispersive X-ray spectroscopy (EDX). The arsenic content was expressed as a percentage. The SEM image obtained by the test is shown in Figure 1 , transmission electron microscopy image is shown in Figure 2 The mass percentage of arsenic is shown in Table 1. Figure 1 It can be seen that PO 4 -SnS@AsG exhibits a fluffy tremella-like structure and PO with a size of 6-15 nm 4 -SnS crystal nanosheets are uniformly attached to the thin layer of graphene. Figure 2 Clearly visible PO 4 -SnS@AsG has three lattice arrangements with lattice spacings of 0.305, 0.287, and 0.367 nm, corresponding to the (101), (111), and (120) planes of SnS crystals. Compared with the SnS lattice data previously recorded in the literature, the spacings are enlarged. This indicates that PO 4 3- The introduction of MgO expands the lattice spacing of SnS.

[0057] The obtained negative electrode material was tested by Fourier transform infrared spectroscopy (FT-IR), and the test results are shown in Figure 3 .Depend on Figure 3Visible, located at 1090 and 1630 cm -1 The vibration at 1083 cm-1 is attributed to the OPO and PO bonds. -1 The vibration at 542 cm -1 The peak at corresponds to the infrared vibration of Sn-O bond, confirming that PO 4 3- After the addition of SnS, Sn-OP covalent bonds are formed with Sn atoms, which serve as conductive pillars to buffer the volume expansion of SnS.

[0058] Preparation of negative electrode Weigh 8 parts by weight of PO 4 -SnS@AsG, 1 part by weight of superconducting carbon and 1 part by weight of carboxymethyl cellulose binder (CMC) were mixed and dissolved and dispersed in a mixed solution of ethanol / water to obtain PO 4 -SnS@AsG negative electrode slurry. The negative electrode slurry was prepared at 0.8 mg / cm 2 The loading amount is coated on the copper foil current collector and the negative electrode sheet is obtained after drying.

[0059] Battery Assembly The negative electrode sheet is combined with a counter electrode potassium block and a separator, and an electrolyte is added and assembled into a battery casing to obtain a battery.

[0060] Diaphragm material: GF / A (Whatman), purchased from Whatman Ltd., UK.

[0061] Electrolyte: 2 M potassium bis(fluorosulfonyl)imide (KFSI) in triethyl phosphate (TEP).

[0062] Battery performance test method: Cycle performance test: Using the Wuhan Blue Electric Test System in China, the constant current charge and discharge (GCD) curve of the battery was tested at a constant temperature of 28°C. The battery was discharged to 0.01 V at a current density of 100 mA / g, and then charged to 3.0 V at a current density of 100 mA / g. This was recorded as the first cycle, and the first reversible capacity D1 was recorded. Repeat the above charge and discharge process, record the reversible capacity Dn of the nth cycle, and calculate the capacity retention rate of the nth cycle. The capacity retention rate of 600 cycles = D600 / D1x100%.

[0063] High current cycle performance test: The constant current charge and discharge (GCD) curve of the battery was tested at a constant temperature of 28°C using the Wuhan Blue Electric test system in China. The battery was discharged to 0.01 V at a current density of 1000 mA / g, and then charged to 3.0 V at a current density of 1000 mA / g, which was recorded as the first cycle. The above charge and discharge process was repeated, and the reversible capacity of the nth cycle was recorded.

[0064] Rate cycling performance: The constant current charge and discharge (GCD) curve of the battery was tested using the Wuhan Blue Electric Test System in China. The battery was discharged to 0.01 V at current densities of 100, 200, 300, 500, 800, 1000, 2000 and 3000 mA / g, respectively, and then charged to 3.0 V at the same current density, and 10 cycles were repeated at each current density.

[0065] K + Diffusion rate test: The test was conducted on the Wuhan Blue Electric Test System in China. First, the battery system was cross-current charged and discharged at a low current of 50 mA / g for 15 minutes, and then the applied current was cut off and kept still for 2 hours, so that potassium could fully diffuse inside the active material and reach a state of equilibrium. By analyzing the relationship between the electrode potential change and the relaxation time, combined with the physical and chemical parameters of the negative electrode material, the potassium ion diffusion coefficient Dk was calculated. Among them, D K The value of can be calculated based on the simplified Fick's second law as follows:

[0066] in: t represents the pulse duration, m B, V M, and M B are the mass, molar volume and molar mass of the corresponding electrode, A is considered to be the interfacial area between the electrode and the electrolyte, ΔE s Indicates the voltage change (V) caused by the current pulse, ΔE t It indicates the voltage change (V) during constant current discharge / charge after deducting the voltage change (iR drop) caused by the internal resistance of the battery.

[0067] Example 2: All steps are the same as those of Example 1, except that the phytic acid solution is replaced by a phosphoric acid solution in the preparation of the negative electrode material.

[0068] Example 3: All steps are the same as in Example 1, but the preparation material is changed to 65 mL GO dispersion with a concentration of 0.8 mg / mL.

[0069] Embodiment 4: A negative electrode material was prepared in a similar manner to that of Example 1, and a battery was prepared using the prepared negative electrode material, except that the annealing temperature in the preparation of the negative electrode material was changed to 600°C.

[0070] Example 5 A negative electrode material was prepared in a similar manner to Example 1, and the prepared negative electrode material was prepared into a battery, except that a high-energy ball milling treatment was performed before the precursor solution was subjected to a hydrothermal reaction. The treatment method was: using a vibrating high-energy ball mill, a ball milling ball with a diameter of 1 mm and the precursor solution were placed in a high-energy ball mill tube at a mass ratio of 1:1, and then high-energy ball milling was performed at a vibration rate of 3000 rpm for 3 minutes.

[0071] Comparative Example 1 A negative electrode material is prepared in a similar manner to Example 1, and the prepared negative electrode material is prepared into a battery, except that no phytic acid solution is added during the preparation of the negative electrode material.

[0072] Comparative Example 2 A negative electrode material is prepared in a similar manner to Example 1, and the prepared negative electrode material is prepared into a battery, except that no graphene oxide solution is added during the preparation of the negative electrode material.

[0073] The EDX test results of Example 1 and Example 5 are shown in Table 1.

[0074] Table 1

[0075] In addition, it can be seen from the data in Table 1 that the arsenic content of Example 5 is higher than that of Example 1. This is because more arsenic is fixed on the graphene through high-energy ball milling. Vibration high-energy ball milling has higher collision energy than rotary ball milling, which effectively produces a mechanochemical reaction, causing arsenic pentoxide particles to collide effectively with graphene particles, thereby increasing the arsenic content fixed on the graphene surface.

[0076] The prepared battery was tested for performance by referring to the battery performance test method described in Example 1. The cycle performance test results of Examples 1-5 and Comparative Examples 1-2 are shown in Table 2, and the rate cycle test results of Examples 1, 3 and Comparative Examples 1-2 are shown in Table 2. Figure 4 The high current cycle performance test results of Example 1, Example 4 and Comparative Example 1 are shown in Figure 5 , K of Example 1 and Comparative Example 1 + The diffusion rate test results are shown in Figure 6 .

[0077] Table 2

[0078] From the results in Table 2 above, it can be seen that in the cycle performance at a current density of 100 mA / g, the specific capacity of Comparative Example 1 continues to decay, and only maintains a specific capacity of 150.4 mA / g after 600 cycles. However, Example 1 maintains a high specific capacity of 374.4 mAh / g after 600 stable cycles, and the capacity decay rate of each cycle is close to zero. This is because the arsenic-doped graphene in Example 1 effectively prevents material aggregation during the cycle, and the PO 4 3- The introduction of groups constructed PO with enlarged interlayer spacing 4 -SnS@AsG three-dimensional conductive material, so that potassium ions have a wider ion channel during the embedding and extraction process, effectively alleviates the pulverization of the material when storing potassium, and ensures the stability of potassium storage. Therefore, Example 1 has a higher capacity retention rate. In Comparative Example 1, there is no large interlayer spacing for phosphate extension, and SnS is inherently poor in conductivity and its layered structure is very prone to serious structural collapse and agglomeration during potassium embedding / depotassium, causing irreversible phase change, causing the active material to pulverize and fall off from the current collector and side reactions to occur continuously. Therefore, the capacity retention rate of Comparative Example 1 is poor. It proves the structural stability of the present invention when storing potassium at low current density. The capacity of the first 200 cycles of Example 5 is higher than that of Example 1, which is provided by more arsenic elements and SnS particles anchored in the surface layer of graphene. However, the integrity of part of the graphene may be destroyed during the high-energy ball milling process, and its capacity retention rate is slightly lower than that of Example 1.

[0079] Figure 4 The rate performance test results of Examples 1 and 3 of the present invention and Comparative Examples 1 and 2 are shown. Figure 4 It shows that in Example 1, PO 4 3- The introduction of the group improves the conductivity of SnS, and the arsenic-doped graphene effectively fixes the SnS particles anchored on the graphene surface layer, preventing particle aggregation during the cycle, so that the material can still maintain high specific capacity and cycle stability after cycling at different current densities, indicating that the material has excellent potassium storage reaction kinetics and structural stability. In the negative electrode materials prepared in Examples 1 and 3, PO 4 3- The introduction of groups constructed PO with enlarged interlayer spacing 4 -SnS@AsG three-dimensional conductive material changes the electronic structure of SnS and improves the conductivity of SnS, thereby obtaining better rate performance. In contrast, Comparative Examples 1 and 2 without adding phosphate or graphene oxide exhibit poor rate performance due to the inherent low conductivity of SnS.

[0080] Figure 5The high current cycle test results of Examples 1 and 4 of the present invention and Comparative Example 1 tested at a current of 1000 mA / g are shown. Figure 5 It shows that the presence of phosphate and graphene oxide in Example 1 improves the conductivity and structural stability of the negative electrode material, thus showing a higher capacity and stable cycling ability at a high current density. In Comparative Example 1, there is no phosphate intercalation to improve the interlayer spacing and conductivity of SnS, thus showing a lower specific capacity.

[0081] Figure 6 K of Example 1 and Comparative Example 1 are shown + Diffusion rate test results. Figure 6 It shows that the K tested under most voltages + The diffusion rate of Example 1 is higher than that of Comparative Example 1. 4 3- The groups effectively expand the interlayer spacing of SnS and improve the conductivity of SnS, making Example 1 have a fast K + The comparative example 1 exhibited a slower K transfer kinetics due to the poor intrinsic conductivity of SnS. + Transfer kinetics. In Example 1, PO 4 3- The introduction of groups gives the negative electrode material an extended interlayer spacing and covalent charge bridges, allowing potassium ions with a larger radius to be quickly transported in the electrode structure and alleviating the lattice expansion during potassium ion insertion, thereby achieving excellent rate performance.

[0082] Example 6 A negative electrode plate was prepared in the same manner as in Example 1, except that the negative electrode plate was pre-potassium treated.

[0083] Positive electrode sheet: 3,4,9,10-perylenetetracarboxylic dianhydride is prepared as an organic positive electrode sheet, wherein the mass of 3,4,9,10-perylenetetracarboxylic dianhydride is twice the amount of the negative electrode loading.

[0084] The pre-potassium-treated negative electrode sheet is combined with the positive electrode sheet and the separator, and the electrolyte is added and assembled into a full battery after being assembled into a battery casing. The separator material is GF / A (Whatman), purchased from Whatman Ltd., UK; the electrolyte is a 2M potassium bis(fluorosulfonyl)imide (KFSI) triethyl phosphate (TEP) solution.

[0085] The prepared full battery was tested according to the above-mentioned rate cycle performance test method, and the test results are shown in Figure 7 .

[0086] Figure 7The schematic diagram of the full battery rate energy density cycle is shown in Example 1, where the pre-potassium-treated electrode is the negative electrode and 3,4,9,10-perylenetetracarboxylic dianhydride is the organic positive electrode. Due to its enlarged interlayer spacing and improved conductivity, the assembled full battery exhibits high energy density and high cycle stability at different current densities.

[0087] In addition, the description of the terms "some embodiments", "other embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In the present application, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments or examples described in the present application and the features of the different embodiments or examples without contradiction.

[0088] The above implementation modes are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned implementation modes, a person skilled in the art should understand that the technical solutions described in the aforementioned implementation modes can still be modified, or some of the technical features can be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various implementation modes of the present application, and should all be included in the protection scope of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material comprises: Arsenic doped graphene, layered tin sulfide anchored on the arsenic-doped graphene, and Phosphate ions are introduced in situ between the stannous sulfide layers.

2. The negative electrode material according to claim 1, characterized in that Relative to the total weight of the negative electrode material, the mass content of the arsenic-doped graphene is 4%-8%.

3. A method for preparing the negative electrode material according to claim 1 or 2, characterized in that: The following steps are involved: Tin source, arsenic pentoxide, sodium hydroxide, phosphorus source and thiourea are sequentially added to a graphene oxide dispersion having a concentration of 0.4 mg / mL-1.0 mg / mL, and the mixture is stirred and dissolved to form a precursor solution. The precursor solution is subjected to a hydrothermal reaction to obtain a precursor powder, The precursor powder is annealed to obtain the negative electrode material.

4. The preparation method according to claim 3, characterized in that: The hydrothermal reaction comprises 160 o C-180 o C for 10-12 h.

5. The preparation method according to claim 3, characterized in that: The annealing treatment includes 2-5 o Annealing at a heating rate of 500 C / min o C-600 o C, keep warm for 4-6 h.

6. The preparation method according to claim 3, characterized in that: The tin source is SnCl4·5H2O.

7. The preparation method according to claim 3, characterized in that: The phosphorus source is selected from phytic acid or phosphoric acid.

8. The preparation method according to claim 3, characterized in that: In the precursor solution, the mass ratio of graphene oxide, tin source, arsenic pentoxide, sodium hydroxide, phosphorus source and thiourea is 1-3:26:24:144:55:

6.

9. The preparation method according to claim 3, characterized in that: Before the hydrothermal reaction, the precursor solution is subjected to high-energy ball milling.

10. A potassium ion battery, characterized in that: Comprising the negative electrode material according to claim 1 or 2, wherein the potassium ion battery comprises a potassium ion secondary battery and a potassium ion full battery.

Citation Information

Patent Citations

  • Heteroelement-containing graphene

    CN111148719A

  • Phosphate ion doped SnS crystal / nitrogen doped rGO composite material as well as preparation method and application thereof

    CN114899365A

  • Cathode active material for potassium ion secondary battery and method for producing the same, and potassium ion secondary battery

    JP2020173902A

  • Method for forming a reduced graphene oxide / metal sulfide composite and its use as an anode for batteries

    US20150318544A1